Rural China: Exploring HIV/AIDS Surveillance and Prevention in a Developing Region - Buffington, Rachel (My University, 2011)
This capstone project was designed to provide a firsthand, true-to-life observational and participatory experience of the planning, structure, implementation, and evaluation of a public health project in a developing, rural setting. It is an in-depth look at a multi-faceted HIV/AIDS surveillance and prevention project taking place in rural China, as directed by the non-governmental organization, Bless China International. Specifically, it examines a project focused on decreasing HIV/AIDS and HIV-related risk behaviors among commercial sex workers, as well as a project focused on HIV/AIDS prevention and awareness and decrease of HIV-related stigmas in ethnic rural villages of southern China. The importance of these projects is rooted in the complex issues that have caused HIV/AIDS to become a major epidemic in southern China and many parts of Southeast Asia. The combination of illegal injectable drug use, commercial sex work, and a high degree of mobility among the population has created a dynamic environment for HIV to spread throughout the general population. These projects aim to reduce the underlying causes of the spread of HIV, such as poverty, lack of awareness, and problems with stigmas related to HIV infection. Data regarding ethnic minority knowledge, attitudes, and practices relating to HIV/AIDS and related risk behaviors was collected and analyzed in a pilot project conducted in 92 rural villages. Forty-six target villages received a one-month intervention focused on increasing knowledge and decreasing stigma of HIV. The results indicate that the intervention was successful in increasing HIV/AIDS knowledge among villagers as well as significantly reducing stigmas related to HIV.
Keywords: Yunnan Province; HIV; Public Health; Prevention; Minority; Village; Health Sciences, Public Health (0573)